PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR NEGERI 018 TANAH MERAH KECAMATANPASIR PENYU KABUPATEN INDRAGIRI HULU - Elvi Rohaya; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Education is a process that is intended to lead to a desired result in accordance with the objectives set. Science education has an important role in realizing the complete Indonesian man, the whole human figure both in terms of mastery of science and morality.Broadly speaking, the factors affecting learning outcomes can be grouped into two: 1) Factors that comes from students themselves and 2) factors that come from outside the student. This study discusses the use of quantum learning model of teaching in elementary school science learning. The aim of this research was to determine whether the use of quantum teaching learning model can improve learning outcomes fifth grade science students of State Elementary School 018 Red Soil District of Sand turtle?.To obtain field data analysis techniques the author uses action research is research conducted by teachers in the class itself through self-reflection in order to improve its performance as a teacher by gradually and continuously through several cycles until the result of increased student learning. Data obtained from research actions on the activities carried out by the teacher colleagues who acted as an observer and formative test results conducted on each cycle.Based on data analysis the authors conclude that the initial test pre-action (preliminary data) learning outcomes of students classified as very low, only 40, or 11% of the 26 students who have mastery with a total value in 1809 the average value of 69.57 and then at first cycle (after the action is performed) student learning outcomes starts to increase by 3.5% or 22% of the 26 students have mastery value with the number 1875 so that the average class into 72.11. While the second cycle is very surged Improvements to the number 2035 with the value of the average class into 78.26 with an increase of 12.50%. From these data, the authors conclude that the use of quantum teaching Learning Model Lesson In the eyes of Natural Sciences Material simple plane can improve student learning outcomes at State Elementary School class V 018 red soil, sand turtle subdistrict, district Indra Giri upstream. Keywords : Quantum Teaching Learning Model , Aircraft Simple